1991
DOI: 10.1099/0022-1317-72-8-1959
|View full text |Cite
|
Sign up to set email alerts
|

Selective Induction of Discrete Epitopes of Herpes Simplex Virus Type 1-Specified Glycoprotein C by Interference with Terminal Steps in Glycosylation

Abstract: We have described two types of oligosaccharide modification influencing the antigenicity of the herpes simplex virus type 1 (HSV-1)-specified glycoprotein C (gC-1). First, the expression of several epitopes belonging to antigenic site II of gC-1 is dependent on the peripheral galactose of N-linked oligosaccharides. We have also shown that treatment of HSV-1-infected cells with 5-n-propyl-2'-deoxyuridine (PdU) under certain circumstances results in other modifications of peripheral carbohydrate determinants, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In this case, elimination of one site of N-linked glycosylation resulted in the loss of some but not all epitopes within an antigenic site, demonstrating that altered glycosylation can have a localized effect without affecting other parts of the molecule. Investigation into the glycosylation of gC has indicated that some epitopes are dependent, some are independent, and some are masked by oligosaccharides (32,42). Site II-reactive MAbs bound to the gC-44 mutant glycoprotein normally, which confirms the independence of site II from site I.…”
Section: Discussionmentioning
confidence: 70%
“…In this case, elimination of one site of N-linked glycosylation resulted in the loss of some but not all epitopes within an antigenic site, demonstrating that altered glycosylation can have a localized effect without affecting other parts of the molecule. Investigation into the glycosylation of gC has indicated that some epitopes are dependent, some are independent, and some are masked by oligosaccharides (32,42). Site II-reactive MAbs bound to the gC-44 mutant glycoprotein normally, which confirms the independence of site II from site I.…”
Section: Discussionmentioning
confidence: 70%
“…The results show, however, that antibody responses in humans may also be elicited by the N-terminus and C-terminal intracytoplasmic domain of gC. The relatively low reactivity of human antibodies with the highly divergent portion of the N-terminus of gC-1 might reflect the clustering of O-linked carbohydrates in this region [Olofsson et al, 1991;Rux et al, 1996].…”
Section: Detection Of Linear Antigenic Determinants On Gc By Pep Scanmentioning
confidence: 79%
“…Anti-HSV-1 serum (K310) was produced by immunization of rabbits with sodium deoxycholate-solubilized HSV-1 membrane antigen, prepared from the F strain grown in rabbit kidney cells (26). Rabbit anti-gB (K861), anti-gC (K642), and anti-gD (K169) antisera were prepared and characterized previously (40,41). Antigens for the production of these sera as well as for the production of anti-gE (K860) rabbit antiserum and another anti-gC (K922) rabbit antiserum were prepared by immunoaffinity chromatography as described previously (41).…”
Section: Methodsmentioning
confidence: 99%